The Role of Agroforestry in Sustainable Land Use - Hlaing, Nandar; Zaw, Soe Thu; Aye, Khin Myo (Journal of Selvicoltura Asean, 2024)
Agroforestry has emerged as a vital strategy for promoting sustainable land use, integrating agricultural practices with tree cultivation. This approach addresses critical issues such as land degradation, biodiversity loss, and climate change, making it essential for enhancing ecosystem services and food security. The primary objective of this research is to evaluate the role of agroforestry in sustainable land use practices. This study aims to identify the benefits of agroforestry systems and their potential to enhance environmental, economic, and social outcomes in various contexts. A systematic literature review was conducted, analyzing peer-reviewed articles, reports, and case studies related to agroforestry practices worldwide. Key themes, including ecological benefits, economic viability, and social implications, were identified and synthesized to provide a comprehensive understanding of agroforestry's contributions to sustainable land use. The findings indicate that agroforestry systems significantly improve soil health, enhance biodiversity, and increase carbon sequestration. Economic assessments reveal that agroforestry can provide stable incomes for farmers while promoting food security. Additionally, community engagement in agroforestry practices has been shown to strengthen social resilience and empower local populations. This research concludes that agroforestry plays a critical role in promoting sustainable land use by enhancing ecological health and supporting local economies. To maximize its benefits, policies should encourage the adoption of agroforestry practices and support research on innovative approaches that integrate trees into farming systems effectively.